Intervensi Non Farmakologi untuk Mencegah Hipotermi pada Pasien Post Operasi - Yulianita, Henny; Yudianto, Kurniawan; Sugiharto, Firman; Rahmawati, Novia; Hidayat, Nabila Nur Fadilah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine non-pharmacological interventions to prevent hypothermia in post-operative patients. The method used is a narrative review with the keywords nonpharmacologic hypothermia management, post-operative patients, non-pharmacologic hypothermia management, and post-operative patients. The databases used include PubMed, EBSCO, Taylor & Francis, and Garuda Portal. The research results showed that there were 14 articles comprising various non-pharmacological interventions to prevent hypothermia in post-operative patients, including forced-air warmers, warm intravenous fluids, electric blankets, and hot packs. In conclusion, several interventions, such as administering warm intravenous fluids using forced-air warmers, electric blankets, and hot bags, can help prevent hypothermia in post-operative patients in central surgical installation rooms. Keywords: Hypothermia, Intervention, Non-Pharmacological, Post-Operation